Illusion in Equality of Opportunity in Education - Aryal, Shiva (Rupantaran: A Multidisciplinary Journal, 2020)
This article focuses on the portion of the confusion that has been addressed by the different sociological and philosophical perspectives on equality of opportunity. For this study, I have used the document review approach where books, reports and research articles are reviewed for the purpose. Basically qualitative information is used and adopted for the thematic information analysis process. This article attempts to settle the illusion of equality of opportunity through binary thinking like the egalitarian that believes on how well people’s lives go not just the formally as a support by Marxist view as the protection should have on the basis of socioeconomic position rather than their personal needs. Basic equality and the social democracy theory are concerned on, no one should be discriminated against their sex or gender, race or ethnicity, and socioeconomic background or to be given equal value as a human worth. This article concludes that the illusion of equality of opportunity still remains on which one standard of measurement is best to achieve equal opportunity that one is unanswerable within single pint and events.